Identification of the citrus GRF gene family and its expression in fruit peel thickening mediated by gibberellin - Xin Liu; Yuewen Chen; Bo Yuan; Miao Peng; Yushuang Zhao; Tong Chen; Jiawei Lu; Feifei Li; Xiaopeng Lu; Junfeng Yang (BMC Plant Biology)
Abstract Background Growth-regulating factors (GRFs) play a crucial role in plant growth and development, particularly in cell division and expansion. Citrus fruit cracking, a prevalent issue, adversely impacts both yield and fruit quality. Gibberellins (GAs) are known to ameliorate citrus fruit cracking by inducing thicker peel formation, which is attributed to cell division and expansion. However, the mechanistic link between gibberellins and citrus peel thickening, and whether this process is mediated by GRF genes regulation, has not been definitively established. Results In this study, 8 CsGRFs (Citrus sinensis), 11 CcGRFs (Citrus clementina), and 8 CgGRFs (Citrus grandis) were identified from the citrus genome which divided into six clusters, with the genes of the same cluster sharing similar gene structures. Cis-elements analysis revealed that the promoter regions of GRF genes contained numerous hormone-responsive elements. Tissue expression profiles showed that CsGRF genes had higher expression levels in young tissues, including early fruit tissues, one-year-leaf, ovules, and root tips. RNA-seq and qPCR analyses revealed that the expression levels of CsGRF3, 4, 7, and 8 were significantly regulated in response to GA3 treatment. Notably, CsGRF8 was the most significantly induced by GA3 and highly expressed in the early stages of peel development. These findings indicate gibberellins may exert regulatory effects on peel development through the induction of CsGRF genes. Conclusion This study systematically analyzed the characteristics of the citrus GRF gene family, as well as the changes in citrus peel thickness and the expression patterns of CsGRF genes under gibberellin treatment. These findings provide valuable insights for advancing research on the role of CsGRF genes in regulating citrus peel development, which could help reduce the occurrence of fruit cracking. Clinical trial number Not applicable.